2005
DOI: 10.1590/s1677-55382005000600012
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of the bladder induced by detrusor instability: experimental study in rabbits

Abstract: Detrusor instability induced by partial bladder outlet obstruction caused significant histopathological and immunohistochemical alterations in the bladder of rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Similar results were also reported in several previous studies (de Boer et al. 1994; Amaro et al. 2005; Bouchelouche et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results were also reported in several previous studies (de Boer et al. 1994; Amaro et al. 2005; Bouchelouche et al.…”
Section: Discussionsupporting
confidence: 93%
“…The IVO14 groups continued to demonstrate inflammatory infiltration, but the cell types were different, consisting mainly of macrophage. Similar results were also reported in several previous studies (de Boer et al 1994;Amaro et al 2005;Bouchelouche et al 2006;Anumanthan et al 2009). What caught our attention in this study is that amitriptyline did not affect the inflammatory infiltration process, which was interesting because studies have shown that tricyclic antidepressants (TCAs) inhibit the release of inflammatory mediators, such as IL-6, IL-1b and TNF-a (Xia et al 1996;Yaron et al 1999;Tai et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Rat wild-type (pRK7-HA-S6K1-WT) and constitutively active S6K clones (pRK7-HA-S6K1-E389, -E389D3E) 7 were obtained from Addgene. Primary BSMC were transfected using LTX and Plus reagent as recommended by the manufacturer (Invitrogen, Carlsbad, CA).…”
Section: Transfections With Myc-mtor and Ha-s6kmentioning
confidence: 99%
“…The most widely used animal is the rabbit, but the pig, rat, and mouse also have been used [711]. Although there are significant differences among animal models of PBOO, there are many similarities among these models and the obstructive dysfunction seen in humans.…”
Section: Introductionmentioning
confidence: 99%